"Development and validation of the ICAP Technology Scale to measure how teachers integrate technology into learning activities". (January 2023) - Antonietti, Chiara; Schmitz, Maria-Luisa; Consoli, Tessa; Cattaneo, Alberto; Gonon, Philipp; Petko, Dominik
Abstract: Previous research investigating the use of technology in school has focused mainly on the frequency of use of digital tools during lessons rather than investigating how technology is integrated with respect to different kinds of learning activities. Since the impact of technology use on learning depends on how it is used and on what activities supported by technology are implemented in lessons, a measurement instrument assessing how technology is integrated into learning activities is necessary to investigate its impact on teaching and learning processes. According to the interactive, constructive, active, and passive (ICAP) framework, which distinguishes four different learning activities based on the level of students' cognitive engagement, we developed the 12-item ICAP Technology Scale (ICAP-TS) that accounts for all four dimensions of technology integration in lessons. We used confirmatory factor analysis to validate the four-factor structure of the ICAP-TS with a sample of 1059 upper-secondary school teachers from Switzerland. We also examined reliability using classical test theory and Rasch model analysis to assess the scale's psychometric characteristics. We then analyzed the associations between the ICAP-TS and a general use frequency measure of 12 educational technologies to test the criterion validity. The results confirmed the four-factor structure of the ICAP-TS and revealed good instrument accuracy. The most difficult items to endorse are those describing the integration of technology into interactive learning activities. Furthermore, all 12 items significantly correlated with the frequency of use of 12 educational technologies. We recommend the ICAP-TS as a short and reliable measurement scale for assessing how technology is integrated into lessons, considering different learning activities based on the ICAP theoretical model. Highlights: A scale to assess how technology is integrated into learning activities is needed. We developed the ICAP-TS to assess technology integration in learning activities. The ICAP-TS differentiates four learning activities supported by technology use. The four-factor 12-item ICAP-TS showed satisfactory validity and reliability. The ICAP-TS can be used to investigate the effects of technology use on learning.